Simplistic expedient and practical synthesis of (+/-)-alpha-lipoic acid - Chavan, Subhash P.; Shivsankar, K.; Pasupathy, K. (Synthesis-Stuttgart, 2005)
Synthesis of a-lipoic acid has been achieved by a simple sequence of reactions. The synthesis highlights the use of alpha-chloroesters in a Reformatsky reaction. The intermediate keto acid is an intermediate from which both isomers of lipoic acid can be prepared.
Keywords: alpha-chloroesters; alpha-lipoic acid; Ozonolysis; Reformatsky reaction

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone, novel cytokine modulators via sharpless asymmetric epoxidation and L-proline catalyzed mannich reaction - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron, 2006)
A short and efficient enantioselective synthesis of (-)-cytoxazone and its stereoisomer (+)-epi-cytoxazone, novel cytokine modulators, has been described with good yield and enantioselectivity. Ti-catalyzed Sharpless asymmetric epoxidation of allyl alcohol and L-proline catalyzed three-component Mannich reaction constitute the key steps in introducing stereogenicity into the molecule. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Asymmetric synthesis; epoxidation; Mannich reaction; Oxidation; Ozonolysis

Facile and convenient synthesis of (+/-)-Biotin via MgCl2/Et3N-mediated C-C coupling and mitsunobu reaction - Chavan, Subhash P.; Chavan, Prakash N.; Lasonkar, Pradeep B.; Khairnar, Lalit B.; Kadam, Appasaheb L. (Synlett, 2014)
A synthesis of (+/-)-biotin is described starting from simple starting materials viz. cyclohexanone and amino malonic acid ester. The key steps involved are MgCl2/Et3N coupling of amino malonic acid ester derivative and acid chloride, Mitsunobu reaction, ozonolysis, Staudinger reduction, novel urea formation, and subsequent dibenzylation. This approach is economical and involves high-yielding steps and simple reaction conditions.
Keywords: Appel reaction; biotin; Mitsunobu reaction; Ozonolysis; Staudinger reduction

Breaking and making of rings: a method for the preparation of 4-quinolone-3-carboxylic acid amides and the expensive drug ivacaftor - Vasudevan, N.; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2015)
A simple and convenient method to access 4-quinolone-3-carboxylic acid amides from indole-3-acetic acid amides through one-pot oxidative cleavage of the indole ring followed by condensation (Witkop-Winterfeldt type oxidation) was explored. The scope of the method was confirmed with more than 20 examples and was successfully applied to the synthesis of the drug Ivacaftor, the most expensive drug on the market.
Keywords: Amides; Drug design; Fused-ring systems; Oxidation; Ozonolysis

Ozone assisted autohydrolysis of wheat bran enhances xylooligosaccharide production with low generation of inhibitor compounds: a comparative study - Sonkar, Rutuja Murlidhar; Gade, Pravin Savata; Bokade, Vijay; Mudliar, Sandeep N.; Bhatt, Praveena (Bioresource Technology, 2021)
In the present study, ozone assisted autohydrolysis (OAAH) was evaluated for enhanced generation of xylooligosaccharide (XOS) from wheat bran. The total XOS yield with optimum ozone dose of 3% (OAAH-3) was found to be 8.9% (w/w biomass) at 110 degrees C in comparison to 7.96% at 170 degrees C by autohydrolysis (AH) alone. Although, there was no significant difference in oligomeric composition (DP 2-6), significant decrease in degradation products namely furfural (2.78-fold), HMF (3.15-fold), acrylamide (nil) and acetic acid (1.06-fold), was observed with OAAH-3 as a pretreatment option. There was 1-fold higher xylan to XOS conversion and OAAH-hydrolysate had higher DPPH radical scavenging activity than AH. PCA plots indicated clear enhancement in XOS production and lower generation of inhibitors with decrease in treatment temperature. Results of the study therefore suggest OAAH can be an effective pretreatment option that can further be integrated with downstream processing for concentration and purification of XOS.
Keywords: Advanced oxidation; Agro-industry waste; hydrothermal treatment; Ozonolysis; Xylooligosaccharide

Synthesis and biological evaluation of hoshionolactam-based compounds - Jachak, Gorakhnath R.; Elizebath, Drishya; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
In search of novel antitrypanosomal agents based on hoshinolactam (IC50=3.9 nM), we disclose the synthesis and biological evaluations of 14 different analogues of the natural product using combinations of different acids and lactams. Antitrypanosomal activity assays revealed that the synthesized analogues were less potent than the parent natural product.
Keywords: Hoshinolactam; Ozonolysis; Parasitic diseases; Trypanosoma

Continuous flow ozonolysis of cardanol for greener synthesis of bio-based monomers - Kulkarni, Sphurti P.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2024)
Synthesis of bio-based monomers via continuous flow ozonolysis of cardanol using a simple tubular reactor is demonstrated. The direct ozonolysis of cardanol produces unique monomer 8-(3-hydroxyphenyl) octanal (HPOA) and heptanal along with several other oxidation products. Maximum 47% yield of HPOA with 54.3% conversion of cardanol was obtained at 0 degrees C in 9 s. The complete conversion of cardanol was obtained at the ozone to cardanol molar flow ratios greater than 2 at all temperatures varied in the range of -10 degrees C to 20 degrees C. Owing to large gas-liquid ratios, the mass transfer limitation for transfer of ozone from gas to liquid was negligible; however, the extent of axial dispersion in the liquid phase was significant at lower liquid flow rates. The non-ideal behavior was incorporated in the axial dispersion model to predict the conversion of cardanol. Examination of kinetic rates by both ideal plug-flow model and plug-flow with axial dispersion model revealed that the reaction is fast and is least influenced by the axial-dispersion in the reactor at prevailing operating conditions. The findings of the current study show that continuous flow technique enables a simple and safer synthesis of high-value bio-based monomers via ozonolysis of cardanol compared to traditional batch methods.
Keywords: Axial-dispersion model; Cardanol; continuous flow; Helical coil; Ozonolysis